Aircraft crashworthiness: proposal of accident investigation checklist. - Roberta Godinho de Carvalho (2003)
Crashworthiness can be defined as the ability of the airplane in protecting its occupants in crash situations. This concept is only applicable in accidents that are survivable, that is, accidents for which the decelerations peaks are into human tolerance limits. There is na international concern about flight safety, because statistics show that the number of accidents per flight departures hás been Constant since 1975 despite the associated efforts in technology and crew training. Then, assuming this scenario of constant accident rate, the form found by researchers, manufacturers and authorities to protect the passengers in the accidents hás been to invest in the aircraft protection capability. A crashworthiness accident investigation can recover information about the aircraft behavior submitted by impact, and can supply the design team with the necessary information in case of a redesign that seeks safety improvement. This work proposes a crashworthiness investigation checklist that is structured according to the methodology presented by National Transportation Safety Board, and the goal is to establish investigative techniques that can facilitate the collection and analysis of crashworthiness data for accidents occurring in commercial aviation.